Efficacy, Safety, and Retention Rate of Extended-Release Divalproex Versus Conventional Delayed-Release Divalproex: A Meta-Analysis of Controlled Clinical Trials - Zhang, Chen Qi; Li, Hong Yan; Wan, Yong; Bai, Xue Yang; Gan, Lu; Wang, Juan; Sun, Hong Bin (Frontiers in Pharmacology, 2022)
Purpose: A novel once-daily divalproex-extended release (ER) dose formulation has been developed; this formulation prolongs the therapeutic serum levels of the drug, compared with the twice-daily conventional divalproex-delayed release (DR) formulation. This study aimed to systematically examine and compare the efficacy, safety, and retention rates of the ER divalproex (VPA-ER) and conventional DR divalproex (VPA-DR) formulations. Methods: Randomized control trials (RCTs) reporting the efficacy, adverse events (AEs), and medication compliance of ER and DR divalproex were searched in online databases, including PubMed, Embase, and Cochrane Library databases, by searching MeSH words and term words. Observational studies with potential biases were excluded. The meta-analysis was performed using Stata 16.0 software. Findings: Thirteen RCTs, involving 1,028 participants, were included in this meta-analysis. Efficacy, AEs, and drug retention rates were the main study outcomes. According to our study, VPA-ER presented clinically significant benefits compared with the placebo in the population with bipolar disorder (BD) (39.5% versus 27.2%, p < 0.001). A similar efficacy of VPA-ER and VPA-DR in controlling seizures was observed in epilepsy patients (87.4% versus 86.5%, p = 0.769). A significantly lower incidence of AEs was reported in the VPA-ER group than in the placebo group (26.8% versus 34.8%, p = 0.003). By contrast, there was no evidence of difference in safety between VPA-ER and VPA-DR (29.4% versus 30.5%, p = 0.750). In addition, the drug retention rate was significantly lower in the VPA-ER group than in the placebo group (76.0% versus 82.7%, p = 0.020), especially in migraine patients (p = 0.022) and in patients who were treated for fewer than 4 weeks (p = 0.018). Implications: The efficacy of VPA-ER was significantly superior to that of the placebo treatment, which provided efficacy similar to that of conventional VPA-DR. VPA-ER is well tolerated with a low rate of AEs compared to the placebo. In addition, the acceptable medicine compliance of VPA-ER was conducive to the long-term maintenance treatment of chronic diseases. Although we analyzed open labels and crossover design RCTs, large-scale multicenter studies on the efficacy and medicine compliance of new ER formulations with less AEs are required to validate our conclusion.